Prenatal Screening: An Ethical Agenda for the Near Future - Jong, Antina de (Bioethics, 2015)
Prenatal screening for foetal abnormalities such as Down's syndrome differs from other forms of population screening in that the usual aim of achieving health gains through treatment or prevention does not seem to apply. This type of screening leads to no other options but the choice between continuing or terminating the pregnancy and can only be morally justified if its aim is to provide meaningful options for reproductive choice to pregnant women and their partners. However, this aim should not be understood as maximizing reproductive choice per se. Only if understood as allowing prospective parents to avoid suffering related to living with (a child with) serious disorders and handicaps can prenatal screening be a publicly or collectively funded programme. The alternative of moving prenatal testing outside the healthcare system into the private sector is problematic, as it makes these tests accessible only to those who can afford to pay for it. New developments in prenatal screening will have to be assessed in terms of whether and to what extent they either contribute to or undermine the stated aim of providing meaningful options for reproductive choice. In the light of this criterion, this article discusses the introduction of the new non-invasive prenatal test (NIPT), the tendency to widen the scope of follow-up testing, as well as the possible future scenarios of genome-wide screening and ‘prenatal personalised medicine’. The article ends with recommendations for further debate, research and analysis.